Ergonomic working posture analysis on highway construction work using the OWAS method - Muhammad Arif Munanda; Mohd. Iqbal; M. Dirhamsyah (Jurnal Polimesin, 2024)
Road construction work has a high risk of injury due to nonergonomic work postures, such as hunched and twisted postures. Such injuries negatively impact workers’ health and can also lead to decreased productivity, higher medical costs, and delayed project completion. This study is important to conduct because of the lack of attention to ergonomics in the construction sector, especially in Indonesia, which results in an increased risk of work accidents and musculoskeletal injuries. Using the Ovako Working Posture Analysis System (OWAS), this study aims to analyze work postures in various road construction activities and identify work positions that have the potential to cause injury. The results of OWAS observations and analysis show that several main jobs, such as road construction (AC 4 = 63.6%), asphalt leveling with screws (AC 4 = 78.6%), and narrow side casting (AC 3 = 21.4%; AC 4 = 42.9%), have a high risk of poor posture. This study suggests ergonomic interventions such as posture training and the use of heavy equipment to reduce the risk of injury and improve work efficiency. The conclusion of this study is expected to provide an overview of the postural distribution of road construction workers, as well as identify the riskiest work postures, so that effective recommendations can be proposed to improve work safety and productivity.